Determination of the spin and parity of all-charm tetraquarks - A. Hayrapetyan; V. Makarenko; A. Tumasyan; W. Adam; J. W. Andrejkovic; L. Benato; T. Bergauer; M. Dragicevic; C. Giordano; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Nature, 2025)
Abstract The traditional quark model 1,2 accounts for the existence of baryons, such as protons and neutrons, which consist of three quarks, as well as mesons, composed of a quark–antiquark pair. Only recently has substantial evidence started to accumulate for exotic states composed of four or five quarks and antiquarks 3 . The exact nature of their internal structure remains uncertain 4–29 . Here we report the first measurement of quantum numbers of the recently discovered family of three all-charm tetraquarks 30–32 , using data collected by the CMS experiment at the Large Hadron Collider from 2016 to 2018 (refs. 33,34 ). The angular analysis techniques developed for the discovery and characterization of the Higgs boson 35–37 have been applied to the new exotic states. Here we show that the quantum numbers for parity P and charge conjugation C symmetries are found to be +1. The spin J of these exotic states is determined to be consistent with 2 ħ , while 0 ħ and 1 ħ are excluded at 95% and 99% confidence levels, respectively. The J P C = 2 ++ assignment implies particular configurations of constituent spins and orbital angular momenta, which constrain the possible internal structure of these tetraquarks.